1968
DOI: 10.1111/j.2042-7158.1968.tb09674.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutual suppression of cardiovascular effects of some β-adrenoreceptor agonists in the cat

Abstract: Observations were made of the effects of adrenaline, isoprenaline and orciprenaline on the blood pressure, heart rate and configuration of the ECG in cats. The effects of single injections of these amines in producing a rise in heart rate and a fall in blood pressure were reduced during the intravenous infusion of any one of them : the pressor response to injected adrenaline was enhanced during an infusion. Combinations of these amines did not produce changes in the configuration of the ECG. These experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Kingsley et al (1972) were unable to demonstrate tachyphylaxis to the acute heart rate effects of isoprenaline in normal human subjects. Atkinson & Rand (1968) observed decreased heart rate effects to injected isoprenaline (as well as to other catecholamines) given -during an isoprenaline--infusion in cats ( Figure 5 of their paper). The heait-rate response to injected isoprenaline was also decreased when it was injected during orciprenaline infusion ( Figure 6 of their paper).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Kingsley et al (1972) were unable to demonstrate tachyphylaxis to the acute heart rate effects of isoprenaline in normal human subjects. Atkinson & Rand (1968) observed decreased heart rate effects to injected isoprenaline (as well as to other catecholamines) given -during an isoprenaline--infusion in cats ( Figure 5 of their paper). The heait-rate response to injected isoprenaline was also decreased when it was injected during orciprenaline infusion ( Figure 6 of their paper).…”
Section: Discussionmentioning
confidence: 90%
“…Kingsley, Littlejohns & Prichard (1972) also studied heart rate increases in normal subjects to isoprenaline and concluded that there was no tachyphylaxis in terms of the dose required to produce a given peak heart rate. Tachyphylaxis to heart rate effects of isoprenaline has also been reported in dogs (Conolly et al, 1971) and cats (Atkinson & Rand, 1968).…”
Section: Introductionmentioning
confidence: 83%
“…This was confirmed by Bouhuys, Douglas & Lewis (1972), but not by Pun, McCulloch & Rand (1971). Tolerance to the chronotropic actions of isoprenaline has also been reported as occurring in man and dogs (Conolly et al, 1971) and in cats (Atkinson & Rand, 1968). More recently, however, Minatoya & Spilker (1975) did not observe tolerance to the chronotropic or bronchodilator actions of isoprenaline in in vivo experiments on healthy dogs.…”
Section: Introductionmentioning
confidence: 82%
“…In these patients a normal bronchodilator response was followed by severe bronchoconstriction. A suggested mechanism is that following a period of ,B stimulation the , adrenoceptors become refractory to stimulation and thus unresponsive to endogenous and exogenous sympathetic stimulation (Atkinson & Rand, 1968;Conolly, Davies, Dollery & George, 1971). In normal human subjects the dose of isoprenaline by bolus injection to produce tachycardia was increased following an i.v.…”
Section: Discussionmentioning
confidence: 99%